Hurray for today! - Worth, Bonnie; Ruiz, Aristides; Mathieu, Joseph (New York : Random House, 2004)
The Cat in the Hat explains the origins of various holidays throughout the year, some well-known and some lesser-known, as well as some of the rituals associated with each.
Includes bibliographical references (p. 43) and index.
13 18 27 30
Keywords: Holidays -- United States -- Juvenile literature; Holidays